A "drug cocktail" delivered by microspheres for the local treatment of rat glioblastoma. (November 2013) - Allhenn, Daniela; Neumann, Dirk; Béduneau, Arnaud; Pellequer, Yann; Lamprecht, Alf
<x xml:space="preserve">Abstract</x> For the treatment of glioblastoma multiforme, an "anticancer drug cocktail" delivered by biodegradable poly-lactide-co-glycolide (PLGA)-microspheres is proposed. Celecoxib, etoposide, and elacridar were encapsulated by an oil/water emulsification solvent evaporation method. Drug-loaded microspheres were analyzed for their physicochemical properties and evaluated in a rat glioblastoma model. Microspheres had a mean diameter 10–20 µm, and encapsulation rates varied upon lipophilicity of the drug (celecoxib: 97.4 ± 0.4%; elacridar: 98.1 ± 0.3%; and etoposide: 38.7 ± 8.3%). Drug release of celecoxib and elacridar resulted in a burst (t50: 3.1 h and 1.0 h, respectively) while etoposide release was slower (t50: 45.3 h). The comparison of celecoxib (p = 0.021) and etoposide microspheres (p = 0.002) as well as their combination (p = 0.011) led to a significant increase in the probability of survival compared to blank microspheres. Local delivery of celecoxib and etoposide microspheres was found to be suitable for the treatment of glioblastoma in rats although simultaneous drug administration did not improve the therapeutic outcome.